2015
DOI: 10.1111/mmi.12885
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli radD(yejH) gene: a novel function involved in radiation resistance and double‐strand break repair

Abstract: Summary A transposon insertion screen implicated the yejH gene in the repair of ionizing radiation-induced damage. The yejH gene, which exhibits significant homology to the human transcription-coupled DNA repair gene XPB, is involved in the repair of double strand DNA breaks. Deletion of yejH significantly sensitized cells to agents that cause double strand breaks (ionizing radiation, UV radiation, ciprofloxacin). In addition, deletion of both yejH and radA hypersensitized the cells to ionizing radiation, UV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 79 publications
1
53
0
Order By: Relevance
“…All of the proteins that interact with SSB to date have a role in some aspect of DNA metabolism. Therefore, an interaction with the C terminus of SSB provides an increasingly reliable indicator of DNA metabolic function.The radD gene (formerly yejH) was recently implicated in the repair of DNA double-strand breaks after radiation or chemical damage (10,11). The peptide sequence of the RadD protein includes all seven of the motifs associated with a superfamily 2 (SF2) helicase (10).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…All of the proteins that interact with SSB to date have a role in some aspect of DNA metabolism. Therefore, an interaction with the C terminus of SSB provides an increasingly reliable indicator of DNA metabolic function.The radD gene (formerly yejH) was recently implicated in the repair of DNA double-strand breaks after radiation or chemical damage (10,11). The peptide sequence of the RadD protein includes all seven of the motifs associated with a superfamily 2 (SF2) helicase (10).…”
mentioning
confidence: 99%
“…The radD gene (formerly yejH) was recently implicated in the repair of DNA double-strand breaks after radiation or chemical damage (10,11). The peptide sequence of the RadD protein includes all seven of the motifs associated with a superfamily 2 (SF2) helicase (10).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the study of Alcantara-Diaz et al (2004) and in terms of the development of E. coli resistance to UV doses relevant to water treatment standards, Chen et al (2015) observed that a genetically modified UVC-resistant E. coli strain possessing the radD/radA genes was relatively unaffected by exposure to 10 mJ/cm 2 (i.e. highest dose tested).…”
Section: Discussionmentioning
confidence: 99%